2023
DOI: 10.1158/1078-0432.ccr-22-3192
|View full text |Cite
|
Sign up to set email alerts
|

PI3K Inhibition Restores and Amplifies Response to Ruxolitinib in Patients with Myelofibrosis

Abstract: Purpose: Treatment options are limited beyond JAK inhibitors for patients with primary myelofibrosis (PMF), or secondary MF. Preclinical studies have revealed that PI3Kδ inhibition cooperates with ruxolitinib, a JAK1/2 inhibitor, to reduce proliferation and induce apoptosis of JAK2V617F mutant cell lines. Patients and Methods: In a phase I dose-escalation and expansion study, we evaluated the safety and efficacy of a selective PI3Kδ inhibitor umbralisib in combination with ruxolitinib in MF patients who had a … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Our multiomic and functional results identified PI3K/AKT/mTOR signaling as a key driver of platelet hyperreactivity in MPNs. The effects of dual PI3K/ mTOR inhibition by omipalisib underscores the essential role of PI3K/AKT/mTOR signaling in mediating platelet metabolism and hyperactivation in MPNs, suggesting potential therapeutic role in MPNs (49,50). We also identified metabolic changes consisting of enhanced OXPHOS and glycolysis activity in MPN platelets.…”
Section: Blood Collection and Platelet Isolation From Humansmentioning
confidence: 72%
“…Our multiomic and functional results identified PI3K/AKT/mTOR signaling as a key driver of platelet hyperreactivity in MPNs. The effects of dual PI3K/ mTOR inhibition by omipalisib underscores the essential role of PI3K/AKT/mTOR signaling in mediating platelet metabolism and hyperactivation in MPNs, suggesting potential therapeutic role in MPNs (49,50). We also identified metabolic changes consisting of enhanced OXPHOS and glycolysis activity in MPN platelets.…”
Section: Blood Collection and Platelet Isolation From Humansmentioning
confidence: 72%
“…Furthermore, the simultaneous targeting of multiple pathways may offer a new therapeutic strategy to maximize the efficacy of JAK inhibition, particularly in patients with a loss of response to JAK inhibitors. Promising clinical outcomes were observed in patients with MF who were treated with ruxolitinib in combination with parsaclisib (PI3Kδ inhibitor), umbralisib (PI3Kδ inhibitor), pelabresib (BET inhibitor), and navitoclax (BCL-X 1 /BCL-2 inhibitor) [37][38][39][40]. Preliminary data also suggest that an investigation of the use of TP-3654 in combination with ruxolitinib is warranted [41].…”
Section: Discussionmentioning
confidence: 99%
“…It initially showed improved PFS but later demonstrated safety concerns and inferior OS [157,158]. Phase II trial investigating the addition of umbralisib to JAK1/2 (Janus Kinase 1/2) inhibitor ruxolitinib in patients with myelofibrosis (MF) demonstrated that combination treatment was well tolerated with an ORR of 37% and that umbralisib may re-sensitize patients with MF to JAK1/2 inhibitor ruxolitinib [159]. However, the FDA withdrew its approval on 1 June 2022, due to increased serious adverse events and risk of death with the use of umbralisib with updated findings from the UNITY-CLL trial [158].…”
Section: Pi3kδ Inhibitorsmentioning
confidence: 99%